Quantitative muscle mass biomarkers are independent prognosis factors in primary central nervous system lymphoma: The role of L3-skeletal muscle index and temporal muscle thickness. Issue 143 (October 2021) - Leone, R.; Sferruzza, G.; Calimeri, T.; Steffanoni, S; Conte, G.M.; De Cobelli, F.; Falini, A.; Ferreri, A.J.M.; Anzalone, N.
Highlights: Low muscle mass is associated with worse survival in primary central nervous system lymphoma. Muscle mass biomarkers may be useful for prognostic stratification in primary central nervous system lymphoma. There is a high correlation between different quantitative muscle mass biomarkers assessed with CT and MRI. Abstract: Objective: To investigate the role of quantitative muscle biomarkers assessed with skeletal muscle index at the third lumbar vertebra (L3-SMI) and temporal muscle thickness (TMT) in predicting progression-free and overall survival in patients with primary central nervous system lymphoma (PCNSL) undergoing first-line high-dose methotrexate-based chemotherapy. Methods: L3-SMI and TMT were calculated on abdominal CT and brain high-resolution 3D-T1-weighted MR images, respectively, using predefined validated methods. Standardized sex-specific cut-off values were used to divide patients in different risk categories. Kaplan-Meier plots were calculated, and survival analysis was performed using log-rank tests, univariate, and multivariable Cox-regression models, calculating hazard ratios (HR) and 95% confidence intervals (CI), also adjusting for potential confounders (age, sex, and performance status). Results: Forty-three patients were included in this study. Median follow-up was 23 months (interquartile range 12–40); at median follow-up, rates of progression-free and overall survival for the cohort were 46% and 57%, respectively. Thirteen (30%) and 11 (26%) patients showed L3-SMI or TMT values below the predefined cut-offs. In Cox-regression multivariable analysis patients with low L3-SMI or TMT showed significantly worse progression-free (HR 4.40, 95% CI 1.66–11.61, p = 0.003; HR 4.40, 95% CI 1.68–11.49, p = 0.003, respectively) and overall survival (HR 3.16, 95% CI 1.09–9.11, p = 0.034; HR 4.93, 95% CI 1.78–13.65, p = 0.002, respectively) compared to patients with high L3-SMI or TMT. Conclusions: Quantitative muscle mass evaluation assessed by both L3-SMI and TMT is a promising tool to identify PCNSL patients at high risk of negative outcome. Confirmatory studies on larger independent series are warranted.